Croatia : Economic Vulnerability and Welfare Study - World Bank (Washington, DC, 2013)
This is the first study of poverty, and income distribution in Croatia, which aims to provide an assessment of the country's poverty status, to explain the causes of poverty, and recommend actions to efficiently reduce poverty. In comparing international poverty standards across transition economies, the study finds that the incidence of absolute poverty in Croatia is low, however, these standards may not adequately reflect country-specific conditions. It is estimated that the level of total household expenditure - after paying for essential non-food expenditures - just attain minimal nutritional needs, and it is this level which therefore represent an absolute poverty line. Thus, less than ten percent of Croatia's population fall below this national specific poverty line, and the report shows it would be affordable for the country to eliminate absolute poverty. It presents the historical, and political context for understanding poverty, which examines Croatia's independence conditions, war consequences, and post-war economic policies, to determine the poverty scale, and profile, and economic causes of poverty, to form the basis for a social assessment. Macroeconomic, and structural policies were key determinants of weak employment growth, and, labor market policies have worsened the negative impact of macro-policies on income distribution. Policies to foster opportunities should include a sustained macroeconomic stability; creation of an enabling environment for private businesses; an increased flexibility of the labor market; and, increased investments in human capital.